Confess, Fletch [videorecording (DVD)] - Mottola, Greg; Borow, Zev; Hamm, Jon, 1971-; Wood, Roy, Jr; Mumolo, Annie; Mayeri, Ayden; Izzo, Lorenza, 1989-; Slattery, John, 1962-; MacLachlan, Kyle, 1959-; Harden, Marcia Gay; Mcdonald, Gregory, 1937-2008 (Paramount, 2023)
In this delightful comedy romp, the roguishly charming and endlessly troublesome Fletch becomes the prime suspect in a murder case while searching for a stolen art collection. The only way to prove his innocence? Find out which of the long list of suspects is the culprit from the eccentric art dealer and a missing playboy to a crazy neighbor and Fletch's Italian girlfriend. Crime has never been this disorganized.